A context-based model for framing political victimhood: Experiences from Northern Ireland and the Basque Country - Álvarez Berastegi, Amaia (International review of victimology, 2019)
All societies moving towards peace must establish reparation measures for victims of political violence. This is not an easy task, however; political victimhood is a controversial concept by itself and all victims of this type are mixed up with general politics from both the past and the present. In divided societies, such as Northern Ireland and the Basque Country, controversies about the definition of political victimhood reproduce old divisions from the past. Drawing on these two case studies, this research project gathers together some initial thoughts on the conceptualisation of political victimhood with regard to three different models: the harm-, blame- and context-based models. The primary contribution of the article lies in the formulation of the third model, the context-based framework.